BRAC Rural Development Program (RDP III): 1993 monitoring review - Ritchie, Anne (© BRAC, 2016)
1. BRAC's portfolio of economic activities 2. Cost recovery of sector programs 3. Rural enterprise project 4. Credit 5. Borrowers' approach to activity identification and management of borrowed funds 6. Housing loans 7. Other conclusions and recommendation 8. Recommendations from RDP II mid-term evaluation and/or future reviews